Paralympians are stronger than you know: a comparison of para and nondisabled powerlifting bench press world records - van den Hoek, D.; Garrett, J.; Howells, R.; Latella, C. (The Journal of Strength and Conditioning Research, 2023)
This investigation explored the absolute and relative strength of bench press world record holders for World Para Powerlifting (WPPO) and International Powerlifting Federation (IPF) athletes. Athlete data (mass [in kilograms], competitive weight class, and bench press mass [in kilograms]) for world record holding male and female athletes were extracted from public databases. Absolute and relative strength (kg/kgbw) of athletes was compared using IPF competitive weight classes. On an individual basis, WPPO world record holders demonstrated greater absolute strength than their IPF counterparts in 5 of 8 weight classes for women and 6 of 8 weight classes for men when classified using standard IPF competitive weight classes. Overall, effect sizes for relative strength were greater in WPPO male (19.6%, g = 0.75) and female (9.24%, g = 0.38) athletes but did not reach statistical significance. The greatest relative strength observed was 3.88 kg/kgbw (under 49-kg WPPO) for male and 2.72 kg/kgbw (under 50-kg WPPO class) for female athletes. For IPF athletes, the greatest relative strength was reported in the under 66-kg class for male athletes (3.35 kg/kgbw) and under 63-kg class for female athletes (2.29 kg/kgbw). The physical impairments experienced by WPPO world record holders do not appear to compromise bench press strength compared with able-bodied athletes. Indeed, WPPO world record holders often possess greater relative and absolute strength than their IPF counterparts. Superior para powerlifting bench press records may be, at least in part, the result of training and biomechanical factors and seem to be the only anaerobic strength-based sport where para records exceed that of able-bodied athletes.